Does the perigestational exposure to chlorpyrifos and/or high-fat diet affect respiratory parameters and diaphragmatic muscle contractility in young rats?. (June 2020) - El Khayat El Sabbouri, Hiba; Gay-Quéheillard, Jérôme; Joumaa, Wissam H.; Delanaud, Stephane; Guibourdenche, Marion; Darwiche, Walaa; Djekkoun, Narimane; Bach, Véronique; Ramadan, Wiam
Abstract: The perinatal period is characterized by developmental stages with high sensitivity to environmental factors. Among the risk factors, maternal High-Fat Diet (HFD) consumption and early-life pesticide exposure can induce metabolic disorders at adulthood. We established the effects of perigestational exposure to Chlorpyrifos (CPF) and/or HFD on respiratory parameters, sleep apnea and diaphragm contractility in adult rats. Four groups of female rats were exposed starting from 4 months before gestation till the end of lactation period to CPF (1 mg/kg/day vs. vehicle) with or without HFD. Sleep apnea and respiratory parameters were measured by whole-body plethysmography in male offspring at postnatal day 60. Then diaphragm strips were dissected for the measurement of contractility, acetylcholinesterase (AChE) activity, and gene expression. The perigestational exposure to CPF and/or HFD increased the sleep apnea index but decreased the respiratory frequency. The twitch tension and the fatigability index were also increased, associated with reduced AChE activity and elevated mRNA expression of AChE, ryanodine receptor, and myosin heavy chain isoforms. Therefore, the perigestational exposure to either CPF and/or HFD could program the risks for altered ventilatory parameters and diaphragm contractility in young adult offspring despite the lack of direct contact to CPF and/or HFD. Highlights: Perigestational exposure to CPF and/or HFD decreased the respiratory frequency and increased the sleep apnea index. Indirectly CPF and/or HFD perigestational exposure programs the risks of ventilatory and respiratory muscles perturbations. The increased diaphragm contractility could be ascribed to altered SR calcium release/uptake. It also could be attributed to modifications in the expression of myosin heavy chain isoforms.